Three-Dimensional In Vitro Lymphangiogenesis Model in Tumor Microenvironment - Cho, Youngkyu; Na, Kyuhwan; Jun, Yesl; Won, Jihee; Yang, Ji Hun; Chung, Seok (Frontiers in Bioengineering and Biotechnology, 2021)
Lymphangiogenesis is a stage of new lymphatic vessel formation in development and pathology, such as inflammation and tumor metastasis. Physiologically relevant models of lymphatic vessels have been in demand because studies on lymphatic vessels are required for understanding the mechanism of tumor metastasis. In this study, a new three-dimensional lymphangiogenesis model in a tumor microenvironment is proposed, using a newly designed macrofluidic platform. It is verified that controllable biochemical and biomechanical cues, which contribute to lymphangiogenesis, can be applied in this platform. In particular, this model demonstrates that a reconstituted lymphatic vessel has an in vivo–like lymphatic vessel in both physical and biochemical aspects. Since biomechanical stress with a biochemical factor influences robust directional lymphatic sprouting, whether our model closely approximates in vivo, the initial lymphatics in terms of the morphological and genetic signatures is investigated. Furthermore, attempting an incorporation with a tumor spheroid, this study successfully develops a complex tumor microenvironment model for use in lymphangiogenesis and reveals the microenvironment factors that contribute to tumor metastasis. As a first attempt at a coculture model, this reconstituted model is a novel system with a fully three-dimensional structure and can be a powerful tool for pathological drug screening or disease model.